2014
DOI: 10.1038/bmt.2013.237
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells–are they really useful for GVHD?

Abstract: Mesenchymal stromal cells (MSCs) have immunomodulatory effects and are increasingly being used for the treatment of acute and chronic GVHD. Although they seem immuno-privileged, they induce alloresponses, but the risk of immunization is poorly characterized. After infusion, they first reach the lungs, liver and spleen, and are then difficult to trace. Several mechanisms are involved in stromal cells suppressing alloreactivity, such as induction of regulatory T cells, but whether or not this will also affect le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 114 publications
(153 reference statements)
1
25
0
Order By: Relevance
“…Perinatal tissue-derived stromal cells have rapidly gained popularity since 2008 (11). We also switched to placenta-derived DSCs for clinical use (6)(7)(8), because these cells have more reproducible immunomodulatory effects than MSCs, they are much easier to obtain, and they have better expansion capacity (6,9). We now found that apart from already reported beneficial immunomodulatory and tropic properties, DSCs also have a smaller cell size and stronger hemostatic capacity, without eliciting any major adverse events, when prepared according to our optimized protocol.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Perinatal tissue-derived stromal cells have rapidly gained popularity since 2008 (11). We also switched to placenta-derived DSCs for clinical use (6)(7)(8), because these cells have more reproducible immunomodulatory effects than MSCs, they are much easier to obtain, and they have better expansion capacity (6,9). We now found that apart from already reported beneficial immunomodulatory and tropic properties, DSCs also have a smaller cell size and stronger hemostatic capacity, without eliciting any major adverse events, when prepared according to our optimized protocol.…”
Section: Discussionmentioning
confidence: 98%
“…Amniotic membrane has been used for successful management of extensive burn wounds and for wound reconstruction in Africa since the early twentieth century (13). Thus, similarly to BM-MSCs (14), the placenta has beneficial wound healing characteristics due to its anti-inflammatory, anti-microbial, anti-scarring, trophic, and hemostatic properties (3,9). This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other possible antigens include xenobiotic serum components, such as bovine serum albumin (BSA) in fetal calf serum (FCS), which is used for expansion of MSCs. The immunogenicity of stromal cells in clinical settings has not been extensively studied [20], and the induction of alloantibodies has only been investigated in immunocompromised patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent critical survey of the published literature by some of the authors of the very first clinical report [4], in 21 studies of treatment of acute GVHD and 10 studies of chronic GVHD involving, respectively, 190 and 61 patients, median 52 and 23% of complete responses (CRs) and partial responses (PRs), respectively, were observed, in the acute setting, while 26% CR and 48% PRs were reported in the chronic patients. In all patients, MSCs were of bone marrow origin, and no significant correlation has ever been found, among others, for autologous versus third-party origin.…”
Section: Treatment Of Graft-versus-host Diseasementioning
confidence: 92%